2015
DOI: 10.2217/fmb.14.149
|View full text |Cite
|
Sign up to set email alerts
|

A novel Triterpene from Astraeus Hygrometricus Induces Reactive Oxygen Species Leading to death in Leishmania Donovani

Abstract: We claim the present invention as substantial in depth evidences that mushroom derived active molecules can be exploited as target specific, comparatively nontoxic leads for antileishmanial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…In continuation with our line of investigation on antileishmanial leads, we also claimed simultaneously the isolation and structure elucidation of a novel triterpene molecule, astrakurkurone, from an active fraction of A. hygrometricus, with a significant effect against promastigotes (14). We have also reported the involvement of reactive oxygen species (ROS) and mitochondrial dysfunction in astrakurkurone-mediated cell death in promastigotes (16). Astrakurkurone was also found effective against clinically important intracellular amastigotes, with a significantly low IC 50 of 2.5 g/ml and a high selective index of 100 (16).…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…In continuation with our line of investigation on antileishmanial leads, we also claimed simultaneously the isolation and structure elucidation of a novel triterpene molecule, astrakurkurone, from an active fraction of A. hygrometricus, with a significant effect against promastigotes (14). We have also reported the involvement of reactive oxygen species (ROS) and mitochondrial dysfunction in astrakurkurone-mediated cell death in promastigotes (16). Astrakurkurone was also found effective against clinically important intracellular amastigotes, with a significantly low IC 50 of 2.5 g/ml and a high selective index of 100 (16).…”
mentioning
confidence: 71%
“…To date, a very limited approach has been made to establish the mushrooms or mushroom-derived metabolites as therapeutic or immunostimulatory agents against Leishmania infection. As few as only seven reports, including three from our group, have been documented up to 2015 regarding the antileishmanial effect of extracts or active constituents of wild mushrooms (10)(11)(12)(13)(14)(15)(16). The first breakthrough was made by Jin and Zjawiony in 2006, when they isolated a novel compound, 5-heptadeca-8=Z,11=Z,16-trienylresorcinol, from a polypore mushroom, Merulius incarnatus Schweinitz 1822 (Corticiaceae), which inhibited the Leishmania growth in vitro (50% inhibitory concentration [IC 50 ] of 3.6 g/ml) with no toxicity on Vero cells up to 25 g/ml (10).…”
mentioning
confidence: 99%
“…Astrakurkurone seen to be quite effective against clinically important intracellular amastigotes, with significant low IC 50 of 2.5 µg/ml. 69 Further extension of their study demonstrated that astrakurkurone boost the immune efficiency of host cells by generating protective cytokines, interleukin 17 and γ-interferon leading to parasite clearance both…”
Section: 69mentioning
confidence: 99%
“…45 The mechanism behind the promastigocidal activity of astrakurkurone was unveiled by Mallick et al (2015) where the proliferation of L. donovani promastigotes were inhibited by astrakurkurone by selective ROS production leading to mitochondrial dysfunction as well as depleting reduced glutathione. Astrakurkurone seen to be quite effective against clinically important intracellular amastigotes, with significant low IC 50 of 2.5 µg/ml.…”
Section: 69mentioning
confidence: 99%
“…In contemporary terms, they can be regarded as functional foods that can furnish health benefits beyond the traditional nutrients. 10 Mushrooms are known to be rich sources of various bioactive substances like antioxidant, [11][12][13] antimicrobial, 14,15 immunomodulatory, 16,17 and anticancer 18 substances. Despite all the mentioned health promoting effects, this diverse group is still largely unknown as more than half of the species remain undescribed.…”
Section: Introductionmentioning
confidence: 99%